(untitled) (Al-Mansour Journal, 2023)
The world of Smart Home is expanded recently, everybody in the world wishes to have a home that can think, solve problems, manage environment, guard itself, or even anticipate needs. These are desirable features in any home but high electricity failure & blackout and the Iraqi life style which system more difficult to implement, in addition to that already company standard build smart home systems are expensive, hard to install, complicated and cannot solve problems arises in our country this is because of lack of public services and most people spend more time in their homes rather than leaving it for a long time (which most smart homes depends on). The proposed system is a simple, easy to implement, inexpensive, efficient and can be incorporated easily in Iraqi building style to manage our homes and lives. issues such as lightening, temperature management, guarding the house and its perimeter, managing electricity, bringing the luxury of voice activation for many of the house appliances, managing water reserve are desirable features. The main idea is to spread many sensors, actuators and electronic switches around the house connected with standard twisted pair wires that arrive to a central power management board connected to a portable PC that represent the brain of the house controlled by a sophisticated expert software that manage the whole.